2021
DOI: 10.3390/molecules26185635
|View full text |Cite
|
Sign up to set email alerts
|

Orexin-A Regulates Follicular Growth, Proliferation, Cell Cycle and Apoptosis in Mouse Primary Granulosa Cells via the AKT/ERK Signaling Pathway

Abstract: Granulosa cells (GCs) are essential for follicular growth, development, and atresia. The orexin-A (OXA) neuropeptide is widely involved in the regulation of various biological functions. OXA selectively binds to orexin receptor type 1 (OX1R) and mediates all its biological actions via OX1R. This study aimed to explore the expression of OXA and OX1R and their regulatory role in GCs proliferation, cell cycle progression, apoptosis, oocyte maturation, and underlying molecular mechanisms of these processes and elu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 49 publications
1
12
0
Order By: Relevance
“…The ovary is one of the important reproductive organs of female animals, regulating follicle development and hormone secretion ( 23 ). Proliferation and apoptosis are natural physiological processes that occur naturally during the growth and development of ovarian follicles ( 24 ). In particular, the apoptosis of POGCs plays a vital role in the induction of atresia in porcine ovarian follicles ( 25 ).…”
Section: Discussionmentioning
confidence: 99%
“…The ovary is one of the important reproductive organs of female animals, regulating follicle development and hormone secretion ( 23 ). Proliferation and apoptosis are natural physiological processes that occur naturally during the growth and development of ovarian follicles ( 24 ). In particular, the apoptosis of POGCs plays a vital role in the induction of atresia in porcine ovarian follicles ( 25 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, IGF1 silencing attenuated the protective effects of kurarinone on H 2 O 2 ‐induced granulosa cell damage, indicating that kurarinone regulated H 2 O 2 ‐induced granulosa cell damage through increasing IGF1 expression. The PI3K/Akt signaling is associated with granulosa cell survival and death 5,44 . Multiple evidences have confirmed that activated PI3K/Akt pathway attenuated H 2 O 2 ‐induced oxidative stress and apoptosis in granulosa cells 25,43,45 .…”
Section: Discussionmentioning
confidence: 98%
“…The ovarian disorders are the main reproductive pathologies contributing to infertility in female, including follicular atresia 3 . Granulosa cells are essential for follicular development, and dysfunctional granulosa cells are linked to follicular atresia progression 4,5 . The oxidative stress is one of the causal mediators of female reproductive diseases, 6 which leads to apoptosis of granulosa cells and subsequent follicular atresia 7 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This indicated how deficiency in orexin contributes to peripheral insulin resistance. The Akt pathway has also been implicated under orexin-A treatment in the granulosa cells of mice, where orexin-A and OX 1 R impacted the phosphorylation of this pathway and had impacts on downstream proliferation and apoptosis [ 82 ]. The Akt pathway, while it can be linked to ERK1/2 upstream, resulted in varying and different cellular responses than the ERK1/2 pathway [ 83 ].…”
Section: Peripheral Role Of Orexinmentioning
confidence: 99%